2019
DOI: 10.14336/ad.2018.0409
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and the Genetic Nexus of Brain Aging, Neuroinflammation, Neurodegeneration, and Brain Trauma

Abstract: Aging is a complex and integrated gradual deterioration of cellular activities in specific organs of the body, which is associated with increased mortality. This deterioration is the primary risk factor for major human pathologies, including cancer, diabetes, cardiovascular disorders, neurovascular disorders, and neurodegenerative diseases. There are nine tentative hallmarks of aging. In addition, several of these hallmarks are increasingly being associated with acute brain injury conditions. In this review, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 234 publications
(250 reference statements)
1
28
0
Order By: Relevance
“…This present work significantly advances the field. Specific miRNAs play a critical role in brain aging, neuroinflammation, neurodegeneration, and brain trauma [112] miRNAs play major roles in cognitive impairment in both AD-like pathology and dementia with Lewy bodies [113,114]. For example, miR-455-3p may have protective effects against abnormal APP processing and Aβ-toxicity in AD [115].…”
Section: Discussionmentioning
confidence: 99%
“…This present work significantly advances the field. Specific miRNAs play a critical role in brain aging, neuroinflammation, neurodegeneration, and brain trauma [112] miRNAs play major roles in cognitive impairment in both AD-like pathology and dementia with Lewy bodies [113,114]. For example, miR-455-3p may have protective effects against abnormal APP processing and Aβ-toxicity in AD [115].…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic analyses indicated that these AD-associated genes are regulated by multiple TBI-associated miRNAs, notably miR-9 and miR-125, which are downregulated in chronic TBI; this suggests that these AD-associated genes are upregulated. Given evidence that TBI accelerates brain aging 27 , we found that at 24-96 h post-injury and as long as 32 years post-injury, miRNAs implicated in brain aging 28 are still found to be dysregulated. One positive finding is that the persistent upregulation of some miRNAs, such as miR-451, in chronic TBI is a sign of a restorative response; for example, increased levels of miR-451 via diet has been shown to protect cells from oxidative stress 29 .…”
Section: Discussionmentioning
confidence: 93%
“…Neuroinflammation is observed in many neurological disorders, including Alzheimer disease (AD), stroke, multiple sclerosis, Parkinson's disease (PD), and neuroinfections [1][2][3]. As innate immune cells in the central nervous system, microglia play a key role in regulating the pathogenesis of neurological disorders.…”
Section: Introductionmentioning
confidence: 99%